Public health research - National Institute for Health Research (Great Britain) (NIHR Journals Library, 2013)
Public Health Research (PHR) publishes research on the benefits, costs, acceptability and wider impacts of non-NHS interventions intended to improve the health of the public and reduce inequalities in health.
Keywords: Public Health; Research; Medical care : Great Britain : Periodicals; Medicine : Research : Periodicals; Medicine : Research : Great Britain : Periodicals; Health promotion : Great Britain : Periodicals; Health promotion; Medical care; Medicine : Research; Great Britain